GLOBALLASHUV DAVRIDA MILLIY TILLARNI SAQLAB QOLISH MUAMMOLARI - Tursunov Bexzodbek Baxodirovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the fact that the world is becoming a single information space as a result of globalization plays a big role in the fate of languages. For example, in the last millennium, 500 of the world's languages became dead languages, and in the last hundred years, 1000 languages have disappeared into the depths of history. Interlinguistic inequality is a major factor affecting the viability of small languages. It has been researched that a certain language is more important, more prestigious, more convenient, and more attention is paid to it in a certain society or world.